MODEL PENGEMBANGAN DAN PEMANFAATAN WAKAF TUNAI UNTUK PENDIDIKAN TINGGI (STUDI KASUS WAKAF AMERTA AIRLANGGA) - Syadid, Muhamad; Muammar, Muhammad Arfan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACTThe The increasingly difficult economic conditions require educational institutions at the tertiary level to develop a model for collecting funds from the community, one of which is through cash waqf. Airlangga University already has a model of developing and utilizing campus-based cash waqf. So with this waqf solution the community can be helped especially by students to continue their education. From here the authors are encouraged to conduct research on "Models of Development and Utilization of Cash Waqf for Higher Education (Case Study of Waqf Amerta Airlangga.".With the formulation of the problem: first, How to use cash waqf for higher education in Amerta Airlangga Waqf. Second, how to model the development of cash waqf in Amerta Airlangga. The method of this study used qualitative-descriptive because the data was qualitative, the data was not quantitative which used statistic. Practically, the data collection used three methods, they were: interview, observation, and documentation.Based on the results of research in Waqf Amerta Airlangga, it is known that the Community donated funds to the Waqf Amerta Airlangga through PUSPAS which is divided into two types, namely non-endowment social donations and endowment donations. Then some of the non-waqf funds were directly put into social donation accounts which could be directly utilized for the Airlangga University PUSPAS program, by 85%. While the other 15% is for the operations of PUSPAS Airlangga University. The Waqf Fund through the Amerta Endowments program will be managed separately for the fund as an investment in a number of portfolios.Â Key Words : Development and Utilization Model, Cash Waqf, Higher Education